Television commercials as a window on American culture for teaching adult English as a second language students - Bieberly, Clifford J. (Kansas State University, 2008)
Educators teaching English as a second language to adult students must keep course materials relevant, up-to-date and low cost. This research examines the possibility of using television commercials to supplement existing teaching materials, making lessons more culturally relevant. Often direct translations reveal that the translator, while knowing the rules of the language, did not fully understand the nuances of that language's culture. The idea that language and culture are interwoven is well established. While some understanding of one without the other is possible, finding ways to blend language and culture in the classroom can give non-native speakers an aid to understanding implied and literal meanings. This dissertation describes research on how American culture is intertwined in the ubiquitous television commercial and how these 30-second "slices of life" could benefit ESL education. It examines American concepts depicted in television advertisements on the four largest networks and then investigates the relative merits of using TV commercials as a teaching tool. This study uses the Map of Culture, developed by anthropologist Edward T. Hall in 1959, for content analysis of ten primary message systems that can categorize cultural descriptions. A sample of nearly 2,000 national television commercials was recorded from four major networks—ABC, CBS, Fox and NBC—during primetime in November 2001. Only national commercials aired more than six times that month were analyzed for trends in illustrating both manifest and latent cultural meanings, and even cultural taboos. Random examples were then selected to create a suite of ESL classroom materials. Television advertising was chosen for this study because of its accessibility and its ability to provide both visual and auditory content. Materials created for use in the classroom included a discussion model with pretest component, a video of selected commercials, a Q&A format follow-up discussion guide, and a post-test measurement instrument. ESL teachers and students who tested the materials and were surveyed on feasibility, logistics, students' interest level, content, and cultural relevance. Television commercials were found to include cultural content useful in ESL lessons and in class testing showed favorable outcomes. The study results could positively impact ESL pedagogy.
Keywords: Television; Commercials; American; Culture; ESL; Education, Bilingual and Multicultural (0282)